Ultra-fast electron capture by electrosterically-stabilized gold nanoparticles. Issue 27 (3rd June 2015) - Ghandi, Khashayar; Findlater, Alexander D.; Mahimwalla, Zahid; MacNeil, Connor S.; Awoonor-Williams, Ernest; Zahariev, Federico; Gordon, Mark S.
Abstract : Faster than electron solvation transfer to gold nanoparticles in water when stabilized by non-covalent bonds with strong intermolecular interactions. Abstract : Ultra-fast pre-solvated electron capture has been observed for aqueous solutions of room-temperature ionic liquid (RTIL) surface-stabilized gold nanoparticles (AuNPs; ∼9 nm). The extraordinarily large inverse temperature dependent rate constants ( k e ∼ 5 × 10 14 M −1 s −1 ) measured for the capture of electrons in solution suggest electron capture by the AuNP surface that is on the timescale of, and therefore in competition with, electron solvation and electron-cation recombination reactions. The observed electron transfer rates challenge the conventional notion that radiation induced biological damage would be enhanced in the presence of AuNPs. On the contrary, AuNPs stabilized by non-covalently bonded ligands demonstrate the potential to quench radiation-induced electrons, indicating potential applications in fields ranging from radiation therapy to heterogeneous catalysis.